La Destrucción De Maquinaria Como Sanción A La Minería Ilegal Violenta La Garantía Constitucional Del Debido Proceso De Contar Con Un Juez Imparcial Independiente Y Competente - Neyra Romero, Moises David (2020)
This investigative work analyzed the problems that exist when proceeding with the destruction of mining machinery as a sanction for illegal mining, the same that is established in article 57 of the Mining Law, which, according to the researcher's perspective, violates fundamental guarantees established in the constitution, which are basic guarantees of due process, which states that in all administrative and judicial proceedings, there must be an independent and competent impartial judge. The main objective of this research was to carry out a conceptual, legal, doctrinal and descriptive study on the guarantees of due process, focusing mainly on the guarantee established in the Constitution of having an impartial, independent and competent judge. In addition, it was analyzed that the Mining Regulation and Control Agency, an administrative entity, ignores the aforementioned guarantees, which generates a biased action that violates the rights of those involved. This was satisfactorily verified thanks to the application of scientific methods and techniques that served to obtain results and to support the proposed reform of the law. in addition, it was established that the Mining Regulation and Control Agency, as an administrative authority, must respect both the Constitution and the provisions of the Organic Administrative Code, which establishes that in all sanctioning procedures there must be due separation between the investigating body and the sanctioning body, clarifying that they must be carried out by different public officials. It is clear that this is not being respected by ARCOM, since it acts as the investigative body for the process in which the existence of illegal mining is determined, and at the same time it is responsible for sanctioning in accordance with the provisions of article 57 of the Mining Act, in contradiction with article 76, paragraph 7 (k), of the Constitution, which states that everyone has the right to be tried by an impartial, independent and competent judge, which is not currently being respected by the action of the Mining Regulation and Control Agency.